Sistem Kendali On/Off Jarak-Jauh Genset Portabel Menggunakan Komunikasi Frekuensi Radio - Rio Budhi Anto (UIN Sultan Syarif Kasim Riau, 2011)
Due to poisonous carbon monoxide (CO) gas emission, portable generator is usually placed away from the location of transfer switch or placed outdoor. Wireless on/off remote controller for portable generator is necessary as the operator might not need to be at site to on/off the engine. This paper presents wireless on/off remote control system for portable generator using radio frequency communication at frequency of 433 Mhz. ATMEL ATtiny2313 microcontroller is used as process controller. The laboratory test results show portable generator can be controlled up to 70 meters. Keywords: wireless on/off remote controller, portable generator, microcontroller ATtiny2313